Coexistence of Two Different Types of Intracerebral Hematomas Caused by Arteriovenous Malformation - Yanaka, Kiyoyuki; Yasuda, Muneyoshi; Furusho, Kentoaro; Asakawa, Hiroyuki; Matsumaru, Yuji; Noguchi, Masayuki; Nose, Tadao (Nepal Journal of Neuroscience, 2005)
Spontaneous intracerebral hematomas usually produce the sudden onset of devastating neurological symptoms. We describe a case showing slowly progressive clinical symptoms followed by a sudden deterioration caused by two different types of intracerebral hematomas coexisting in the adjacent area. A 72-year-old female with a 2-year history of Alzheimer’s disease and a 3-month history of occasional headache and vomiting was admitted after she experienced the sudden onset of right hemiparesis and a speech disturbance. Neuroradiological examinations demonstrated two different types of intracerebral hematomas coexisting in the left temporal lobe. The patient underwent a left frontotemporal craniotomy. A solid hematoma was found immediately below the cortex and a large hematoma cavity, which contained degraded bloody fluid, was found below the solid hematoma. Histological study demonstrated an arteriovenous malformation (AVM). The AVM may have been responsible for the pathogenesis of these two different types of intracerebral hematomas. Initially, a silent intracerebral hemorrhage from the AVM and liquefaction of the hematoma probably formed the cavity and repeated small subclinical hemorrhages into the cavity during a prolonged period of time may have caused the growth of the inner hematoma. The sudden rupture of the AVM most likely caused the outer solid hematoma, resulting in the abrupt onset of hemiparesis and speech disturbance. This is the first case to demonstrate two different types of intracerebral hematomas coexisting in the adjacent area. A possible mechanism for this rare condition is discussed. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005